2018
DOI: 10.1007/s12026-018-9018-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Chlamydia psittaci plasmid-encoded protein CPSIT_p7 induces partial protective immunity against chlamydia lung infection in mice

Abstract: The present study evaluated the immune-protective efficacy of the Chlamydia psittaci (C. psittaci) plasmid protein CPSIT_p7 and analyzed the potential mechanisms of this protection. The current study used recombinant CPSIT_p7 protein with Freund's complete adjuvant and Freund's incomplete adjuvant to vaccinate BALB/c mice. Adjuvants alone or PBS formulated with the same adjuvants was used as negative controls. Mice were intranasally challenged with 10 inclusion-forming units (IFU) of C. psittaci. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…For optimal protection, chlamydial vaccines must induce Th1-cytokine-biased CD4 + T cells, especially IFN-γ, and humoral responses [ 17 , 29 , 30 ]. Our previous studies also found that both subunit antigens and polypeptide antigens could induce the secretion of Th1-biased cytokines and produce protective effects [ 19 , 31 ]. In addition, we also detected significant differences in the reduced levels of IFN-γ in lung tissues after C. psittaci infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For optimal protection, chlamydial vaccines must induce Th1-cytokine-biased CD4 + T cells, especially IFN-γ, and humoral responses [ 17 , 29 , 30 ]. Our previous studies also found that both subunit antigens and polypeptide antigens could induce the secretion of Th1-biased cytokines and produce protective effects [ 19 , 31 ]. In addition, we also detected significant differences in the reduced levels of IFN-γ in lung tissues after C. psittaci infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have proven that the C. psittaci plasmid proteins CPSIT_p7 and CPSIT_p8 possess desirable immunogenicity as well. The CPSIT_p7 polypeptide vaccine antigen was further constructed, and animal experiments showed good anti-infection protection [ 18 , 19 ]. Donati et al [ 20 ] constructed a pCMV-KA-Pgp3 eukaryotic vector, and then immunized C3H/HeN mice to evaluate the protective effect against C. trachomatis vaginal infection.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant protein CPSIT_P7 was purified as previously described (Tan et al, 2018), and the purity of the CPSIT_P7 protein was detected by SDS-PAGE. Then, the purified CPSIT_P7 protein was treated with the ToxinEraser TM Endotoxin Removal Kit (GenScript, Piscataway, United States), and the endotoxin level was measured using Limulus amebocyte lysate (Chinese Horseshoe Crab Reagent Manufactory, Ltd., Xiamen, China).…”
Section: Purification Of the Recombinant Cpsit_p7mentioning
confidence: 99%
“…BALB/c mice intranasally immunized with recombinant Pgp3 protein purified from chlamydial serovar D exhibited cross-serovar protection against C. muridarum genital tract infection ( 17 ). Furthermore, immunization with Chlamydia psitaci CPSIT_P7, homologous of C. trachomatis Pgp3 with 70% protein sequence identity, provided partial protection against C. psitaci lung infection in BALB/c mice ( 18 ). Therefore, Pgp3 showed stable protective efficacy against both Chlamydia strains and in different mouse models, suggesting the potential value of Pgp3 in clinical vaccine development.…”
Section: Introductionmentioning
confidence: 99%